Improve School Promotion Through Persuasion Texts on Social Media - Sindy Monika, Sindy Monika; Dewi Kusumaningsih; Reni Kusmiarti; Ira Yuniati; Eli Rustinar (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2023)
Improving school promotion with persuasion texts on social networks is a strategy that can have a positive impact on student interest. The purpose of this study is to explain the increase in choosing schools in SMP Negeri 14 Kota Bengkulu. This research uses qualitative descriptive method, this research was conducted at SMP Negeri 14 Kota Bengkulu. This data collection was carried out through observation techniques by coming directly to SMP Negeri 14 Kota Bengkulu schools, conducting in-depth interviews with survey subjects, namely appointed teachers and documentary surveys in the form of photo or video documentation. The use of social media such as Instagram has proven effective in increasing students' interest in school. The use of social media as a sales promotion tool has also proven effective in increasing sales as well as proven effective in increasing sales of online store products. In education, the use of social media as a recruitment tool has been shown to have a significant impact on student engagement.